Hubungan Akhlak Mahasiswa dengan Hasil Belajar - Suhaili, Hidayati (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to describe morals with the learning outcomes of Islamic religious education students of STKIP Abdi Pendidikan Foundation. The method used is the correlation method. The sampling method was using cluster random sampling technique with a total of 36 students. The results of the study found that there was a significant relationship between student morals and learning outcomes of Islamic religious education because the results of hypothesis testing based on r 0.38, obtained tcount 1.697 with degrees of freedom n-2(34-2=32) with a significant level of 0.05. The hypothesis is accepted that tcount is greater than ttable that is, 2.315>1,697. In conclusion, there is a significant relationship between morals and learning outcomes of Islamic religious education students of STKIP STKIP Foundation Abdi Pendidikan Payakumbuh. Keywords: Morals, Learning Outcomes